2006
DOI: 10.1002/pssb.200562446
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic microstructure of NANOPERM‐type nanocrystalline alloys

Abstract: Controlled crystallization of amorphous NANOPERM-type Fe 76 Mo 8 Cu 1 B 15 alloy leads to the formation of crystalline grains of about 10 nm in size. The evolution of crystallization and its impact on the resulting magnetic properties is followed by nuclear and atomic based techniques of (subatomic) structural characterization comprising Mössbauer spectrometry, X-ray diffraction, transmission electron microscopy, high resolution transmission electron microscopy, differential scanning calorimetry, and atomic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Full orientation distribution analysis in as-cast state was not performed due to the absence of higher-order diffraction maxima. It seems that any surface effects related to partial crystallinity on either surface can be fingerprinted (if at all) only by methods with resolution directly related to the size of the quenched-in nanocrystalline phases; AFM seems a convenient instrument for such investigations in future, as indicated previously [1,5], alongside with transmission electron microscopy of both surfaces or in cross-sectional view. It is to be noted that the surface layer with occurrence of quenched-in crystallinity is quite thin, being of the order of $100 nm [4].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Full orientation distribution analysis in as-cast state was not performed due to the absence of higher-order diffraction maxima. It seems that any surface effects related to partial crystallinity on either surface can be fingerprinted (if at all) only by methods with resolution directly related to the size of the quenched-in nanocrystalline phases; AFM seems a convenient instrument for such investigations in future, as indicated previously [1,5], alongside with transmission electron microscopy of both surfaces or in cross-sectional view. It is to be noted that the surface layer with occurrence of quenched-in crystallinity is quite thin, being of the order of $100 nm [4].…”
Section: Resultsmentioning
confidence: 97%
“…An exception is represented by surface-quenched crystals of B 2 Mo 2 Fe, which protrude significantly above the ribbon surface [5], providing however, an interesting example of functionally graded thin ductile material with high surface hardness and roughness.…”
Section: Resultsmentioning
confidence: 99%
“…Surface of amorphous alloys can also be effectively studied by AFM [26][27][28], which can reveal surface features several nanometers in size. AFM images of the ribbon (Fig.…”
Section: Characterization Of Sample In the Initial Statementioning
confidence: 99%
“…Because Fe is in fact a calibration material for Mössbauer spectrometry, this technique is particularly suitable for the investigation of the influence of the composition on hyperfine interactions. In addition, in our earlier works [6][7][8][9], we have demonstrated that the Fe 76 Mo 8 Cu 1 B 15 nanocrystalline alloy is a very good model system particularly for case studies of hyperfine interactions by the help of Mössbauer spectrometry. Taking this into consideration, the present article extends our previous results to more systematic study of the effects of the composition.…”
Section: Introductionmentioning
confidence: 96%